The Mystery Of The Spiteful Letters - Enid Blyton
An adventure for the Five Find-Outers and their dog. Fatty, Larry, Daisy, Pip, Bets and Buster become involved in a very peculiar situation when a series of unsigned letters are sent to various people in Peterswood.